2021
DOI: 10.1111/prd.12391
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders through the periodontal lens

Abstract: People with eating disorders suffer from a mental disorder that negatively affects their physical and/or mental health. The three most frequent eating disorders are binge eating disorder, bulimia nervosa, and anorexia nervosa. Environmental and genetic factors are involved in the pathogenesis of eating disorders in vulnerable persons. Although treatment varies among different types of eating disorders, nutrition, medical care combined with psychotherapy and medications are standard of care. The aim of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 104 publications
(241 reference statements)
0
4
0
1
Order By: Relevance
“…In studies on oral and dental health and eating disorders in the literature, eating disorders are also observed in people with impaired oral health. [19][20][21][22] Patterson Norrie et al 5 reported in their study that individuals with oral health problems have eating disorders. In another study, Brandt et al 21 reported that the relationship between individuals' oral health and eating disorders was significant in terms of care, and those with eating disorders were obsessed with oral health.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on oral and dental health and eating disorders in the literature, eating disorders are also observed in people with impaired oral health. [19][20][21][22] Patterson Norrie et al 5 reported in their study that individuals with oral health problems have eating disorders. In another study, Brandt et al 21 reported that the relationship between individuals' oral health and eating disorders was significant in terms of care, and those with eating disorders were obsessed with oral health.…”
Section: Discussionmentioning
confidence: 99%
“…A whitish appearance of the free gingival margin of the recession is frequent as a sign of chemically induced tissue damage by intrinsic and extrinsic acidity. Atypical localizations such as the palatine surfaces of the upper molars are characteristic of ED patients [58]. Toothbrushing frequency is one of the main risk factors for gingival recession along with improper toothbrushing duration and force [57].…”
Section: Periodontal Healthmentioning
confidence: 99%
“…92 There is limited literature on the role of dentists in the care of patients with EDs and feeding disorders, though existing studies suggest inclusion of a dental care professional in multidisciplinary treatment along with emphasis on education around a home dental care regimen and frequent dental follow-up. 76,93,94 Prevention of further damage requires correction of the underlying behaviors and ED.…”
Section: Oral and Mucosal Symptomsmentioning
confidence: 99%